KECENDERUNGAN STILISTIK KARYA KOMUNITAS FILM DIBOGOR: RELASI SUMBER PENGETAHUAN FILM DENGAN ASPEKGAYA FILM - Damas Cendekia, Damas Cendekia; Hibatullah Salim Wahid Asybili, Hibatullah Salim Wahid Asybili (Akademi Komunikasi SAE Indonesia, 2025)
This article constitutes a summary of the writer's artistic research that has been done previously. The research aimed to find a form of relationship between the source of filmmaking knowledge and film style. The subject of this research focused on filmmakers from film communities in Bogor and their works. Interviews of filmmakers about their filmmaking knowledge and textual analysis of film style in their works were used as the basis. This research has the purpose of identifying the big stylistic tendencies in those films. The tendencies ultimately question the existence of a relationship between the filmmakers' source of knowledge and the stylistic aspects of the films they produce.